Survival Outcome after cardiopulmonary Resuscitation of Medicine Patients in Maharat Nakhon Ratchasima Hospital - Kaewsuwanna, Pinij (Maharat Nakhon Ratchasima Hospital Journal, 2024)
We retrospectively reviewed the 293 patients on whom cardiopulmonary resuscitation (CPR) was performed for the cardiac arrest patients who were admitted to the Department of Medicine from July 1, 2003 to September 30, 2003. There were female for 11.3%. Mean age of our patients were 57.6 years. Most patients were admitted to normal. 94.5%. More than 60% of the patients were seriously ill including pneumonia with respiratory failure (13.7%), cerebrovascular disease (10.9%), chronic obstructive pulmonary disease (8.9%), septic shock (8.2%), sepsis (6.5%), upper gastrointestinal bleeding (6.5%), congestive heart failure (6.1%) and acute coronary syndrome (4.8%). Asystoly was found to be the most common initial rhythm at cardiac arrest (95.5%). Cardiac arrest occurred within 72 hours for 65.5%. Survival outcome of arrested patients at the first hour after successful cardiopulmonary resuscitation in our study was 37.9%, at 24 hours was 6.1%. Only 7 patients in this study could survive and discharged from the hospital. There were several factors that may influence the survival outcome after CPR including age, underlying disease and the severity of the disease, initial rhythm at the cardiac arrest and the skill of CPR performance of the physicians.